Peluang Usaha UMKM Untuk Meningkatkan Pendapatan Rumah Tangga Di Desa Tanjung Makmur: Pelatihan Pembuatan Cemilan Dari Kulit Lumpia - Novie Al Muhariah; Andri Irawan; Anis Feblin; Gitta Destalya Adrian Nova; Hasiatul Aini; Tati Herlina; Yetty Oktarina; Feby Veronika Simanjuntak (Jurnal Pengabdian kepada Masyarakat (DIASYA), 2026)
This community service activity aims to explore business opportunities for MSMEs (Micro, Small, and Medium Enterprises) to increase household income in Tanjung Makmur Village, Sinar Peninjauan District, Ogan Komering Ulu Regency, South Sumatra, through training on making snacks from spring roll wrappers. The main problems faced by the local community are the low level of household income, which relies mainly on the plantation sector, limited skills in identifying MSME  pportunities, and low knowledge of processing food products that have marketable value.The implementation methods include counseling, demonstrations of making snacks from spring roll wrappers, hands-on practice, providing skills in producing high-quality spring roll wrappers using more modern techniques that align with current snack trends popular among the public, assistance in packaging, and the introduction of simple marketing strategies. By utilizing spring roll wrappers, housewives can produce high-value products with broad market potential. This training also opens opportunities to create new home-based businesses, encourages creativity in product diversification, and strengthens the village economy sustainably through community empowerment.